The role of seed transmission in the spread of cereal viruses: Global challenges and prevalent threats in Ukraine - Halyna Snihur; Tetiana Shevchenko; Oleksiy Shevchenko; Anhelina Kyrychenko (Plant Protection Science, 2025)
The transmission of plant viruses through seed plays a fundamental role in virus spread, persistence, and survival, particularly in economically important crops. Besides its considerable ecological significance, seed transmission influences plant and virus evolution. Virus contamination of the seed also has critical epidemiological implications, especially when combined with subsequent or additional insect vector spread. Plants grown from contaminated seeds serve as primary viral inoculum sources, facilitating the introduction of viruses into new regions and triggering disease outbreaks with substantial economic losses for growers. Changes in environmental conditions increasingly influence plant virus epidemiology by affecting vector populations, host susceptibility, and transmission dynamics, thus increasing virus transmission risks in cereal crops. This review explores the mechanisms of seed transmission and its consequences, with a focus on key cereal viruses in Ukraine: barley stripe mosaic virus, wheat streak mosaic virus, High Plains wheat mosaic virus, sugarcane mosaic virus, and maize dwarf mosaic virus. Hereby, the biological properties of these viruses, the risks posed by seed transmission, and the economic impact on crop production are discussed. Given the widespread distribution of these pathogens, presented data will also be valuable for other cereal-growing regions, particularly those bordering Ukraine and engaged in seed import/export. This review underscores the global need to manage seed-transmitted viruses to safeguard cereal crop productivity and food security. Future research should focus on developing resistant cultivars and advanced diagnostics to control their spread.